Ответ:
1) (3,6 : 0,4 - 2,3) * 2 + 6,6 = (9 - 2,3) * 2 + 6,6 = 6,7 * 2 + 6,6 = 13,4 + 6,6 = 20
2) (3,5 : 0,5 - 0,2) : 2 + 5,9 = (7 - 0,2) : 2 + 5,9 = 6,8 : 2 + 5,9 = 3,4 + 5,9 = 9,3
3) (1,2 : 0,4 - 1,2) : 3 + 0,4 = (3 - 1,2) : 3 + 0,4 = 1,8 : 3 + 0,4 = 0,6 + 0,4 = 1
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Ответ:
1) (3,6 : 0,4 - 2,3) * 2 + 6,6 = (9 - 2,3) * 2 + 6,6 = 6,7 * 2 + 6,6 = 13,4 + 6,6 = 20
2) (3,5 : 0,5 - 0,2) : 2 + 5,9 = (7 - 0,2) : 2 + 5,9 = 6,8 : 2 + 5,9 = 3,4 + 5,9 = 9,3
3) (1,2 : 0,4 - 1,2) : 3 + 0,4 = (3 - 1,2) : 3 + 0,4 = 1,8 : 3 + 0,4 = 0,6 + 0,4 = 1
https://dzen.ru/media/id/6432d25005dc1d4e1117b8fa/razoblachenie-znaniikom-1-chast-6432d2c32fc1bb4859da5aaf